Leading-Edge Strategies for Enhancing Higher Education Institutions' Management Systems - Shaturaev, Jakhongir (Universitas Pendidikan Indonesia (UPI), 2023)
This paper deeply analyses the latest strategies for enhancing the management system of higher education institutions. This study sets out the importance of the management system of higher education institutions (HEIs); (b) states the leading-edge strategies for modernizing the management system of HEIs; (c) calls attention to changing the mindset of the university pedagogical staff and leaders and using broader methods in reforming management system of HEIs; (d) suggests further approaches for superior academic outcomes. This study gathered data through field trip HEIs observations, interviewing HEIs rectors, lecturers, and university staff, and analyzing available data. The qualitative research findings reveal dissatisfaction with the present strategies and leading to poor academic achievements in the HEIs of Uzbekistan. Meanwhile, within the framework of the article, based on the methods of analysis and synthesis, generalization, and deduction, the main features and elements of the university management system, as well as current approaches to the management of a modern university, will be studied. Found data shows that improper infrastructure of government expenditure on education, low salary, and limited quota in pedagogical universities lead to a shortage of teachers and poor academic achievements.